A protocol for estimating health burden posed by early life exposure to ambient fine particulate matter and its heavy metal composition: a mother–child birth (ELitE) cohort from Central India - Trushna, Tanwi; Yadav, Vikas; Mandal, Uday Kumar; Diwan, Vishal; Tiwari, Rajnarayan R.; Ahirwar, Rajesh; Raj, Dharma; Rana, Sindhuprava; Surve, Suchitra Vishwambhar; Dey, Sagnik; Sabde, Yogesh Damodar (Frontiers in public health, 2025)
Pregnant women and children are vulnerable to air pollution-related adverse health effects, especially those residing in low-resource and high-exposure settings like India. However, evidence regarding the effects of early-life exposure to air particulate matter (PM) on childhood growth/developmental trajectory is contradictory; evidence about specific constituents of PM, like heavy metals, is limited. Similarly, there are few Indian cohorts investigating PM exposure and the incidence of acute respiratory infection during infancy. This study protocol aims to fill these critical gaps in knowledge. We aim to establish a mother-child birth cohort through the enrolment of 1,566 pregnant women residing in two urban areas of central India. Antenatally, we will collect socioeconomic, demographic, and clinical information and details of confounding variables from these pregnant women, who will then be followed up until childbirth to assess their exposure to air PM. Biomonitoring will also be conducted to evaluate heavy metal exposure. At birth, pregnancy outcomes will be noted, followed by postnatal follow-up of live-born children until the first year of life to assess their achievement of growth/development milestones and exposure to pollutants. We will also estimate the incidence of Acute Respiratory Infections (ARI) during infancy. This manuscript describes the protocol for an Indian mother-child air pollution birth cohort study that aims to generate comprehensive evidence regarding the adverse effects of early-life (i.e., both pre- and post-natal) exposure to air PM and its constituent heavy metals among Indian children. This study will provide an epidemiological basis for further understanding in this context. Finally, by reporting our carefully planned study methods/outcome measures, which are comparable to those of published and ongoing birth cohorts, we aim to serve as the starting point for similar cohorts in the future, which, when considered together, would generate enough evidence to facilitate context-specific policy-making and development of appropriate prevention and mitigation strategies.